Aplikasi Sistem Manajemen Mutu ISO 9001:2008 untuk Menganalisis Kinerja Pabrik Readymix Concrete - Utami, Sholaekhah Ambar; Priyo, Mandiyo (Semesta Teknika, 2013)
ISO 9001:2008 define the requirements and recommendation for design and valuation of the quality management system to ensure that the corporation provides the products (goods/services) that meet the needs and also to increase the productivity efficiently. This study aimed to analyse the corporation performance in quantitative and qualitative, to discover the impact and the application of quality management system based on ISO 9001:2008 in PT. Jaya Ready Mix. The method used in this research was descriptive method and data were collected by field observation, interview with staff in technical and quality department. The secondary data also obtained from the record of the corporation. The results show that qualitative and quantitative measurement presented improved performance. It means that both show the parallel trend. Thus it can be concluded that application of quality management system ISO-9001-2008 by PT Jaya Readymix are already in the right condition. The impact of this application was the increasing of quality continuously such as the procedure for saving records, work instruction and controlling in fabrication for ready-mix concrete and also the documents for quality manual, business practices, operating procedures, standards, descriptive information and quality record.